Obesity during pregnancy and lactation increases the inflammatory response and reduces the efficacy of nimesulide in the offspring of wistar rats (Revista Contexto & Saúde, 2025)
The type of diet consumed during pregnancy and early life increases the possibility of developing metabolic syndrome, which can result in altered efficacy of some drugs. The aim of this study was to evaluate the inflammatory response in the offspring of Wistar rats fed a Western diet (WFD) and the anti-inflammatory effect of nimesulide. Twenty Wistar rats and their male offspring were used. The dams were divided on the 1st day of gestation into two groups: 1) DPgl: received standard diet (SD) and 2) DOgl: received DO, both from gestation to the end of lactation. On the 21st day of lactation, the male offspring were divided into six groups (n=5 animals/group) and assigned to different experimental protocols, in order to assess on the 60th day of life the influence of the type of diet on the inflammatory response (through carrageenan-induced paw oedema) and the anti-inflammatory action of nimesulide (5 mg/kg, i.p), by quantifying the levels of IL-6, TNF-α and myeloperoxidase (MPO) in the plantar tissue of the rats. The volume of edema was greater in the offspring of DOgl dams, regardless of whether they received PD or DO post-weaning; in those that received DO, the activity of nimesulide was reduced and the levels of IL-6, TNF-α and MPO were elevated. In the offspring of DPgl dams, which received PD post-weaning, the anti-inflammatory activity of nimesulide, verified in the paw volume, was maintained at all three evaluation times. Thus, the inflammatory response was more significant in the DOgl offspring that received DO, and these animals showed a reduction in the anti-inflammatory effect of nimesulide.
Keywords: Western Diet; Acute inflammation; Nimesulide